Guidebook 10. Field Trip Guidebook for the Western Vermilion District, Northeastern Minnesota - Southwick, D.L.; Ojakangas, R.W. (Minnesota Geological Survey, 1979)
Prepared for the 25th Annual Meeting of THE INSTITUTE OF LAKE SUPERIOR GEOLOGY and THE GEOLOGICAL SOCIETY OF AMERICA, NORTH-CENTRAL SECTION Duluth, Minnesota, 1979, 65 p. SPECIAL PAPERS: Southwick, D.L., The Vermilion Granitic Complex, northern Minnesota; Bauer, R.L., Structural studies in the Norwegian Bay block of the Vermilion Granitic Complex, northern Minnesota; Morey, G.B., The western Vermilion district—a review; and Ojakangas, R.W., Archean sedimentation in the Vermilion district. The Vermilion Granitic Complex consists of granitic and migmatitic rocks of Archean age (2,700 m.y.) that are the westward extension into Minnesota of the Quetico gneiss belt of Ontario. The complex is chiefly light grayish-pink biotite granite (following the rock classification of Streckeisen, 1973) that grades into migmatite with increasing content of schistose inclusions. The major grayish-pink granite and its genetically related grani te rich migmati te were named the Vermilion Grani te by Grout (1923), who was the first to study the rocks in detail (Grout, 1923; 192~b,1926). Because migmatites are so abundant within the area Grout mapped as granite, and because other rock types such as quartz diorite and trondhjemite are important locally, the term Vermilion Granite has been replaced formally by the more inclusive term Vermilion Granitic Complex. Where the grayish-pink biotite granite that is the dominant component of Grout's Vermilion Granite is homogeneous, it has been renamed the Lac La Croix Granite, and it is understood to be a subunit within the Vermilion Granitic Complex.